Importancia de la producción oral de textos narrativos basados en el recurso literario del cuento, en niños, con apoyo del docente en el proceso de redacción a partir de su creatividad - Lara Calderón, Pablo Lleral; Cordero Rodríguez , Ruth Elena; Rueda Salazar, Andrea Juliana; Portilla Mártinez, José Vicente; Aguilera, Oscar (Reflexiones metodológicas y epistemológicas en torno a las prácticas pedagógicas contemporaneas, 2021)
The importance of reading in children is due not only to neurolinguistic studies, but also to socio-pedagogical reasons, where it is important that the structure formed by teachers manages to amalgamate from the cultural point of view the relationship between the reading motivation exerted from the family nucleus, with a leverage with the motivational empowerment operationalized from the classroom, with the purpose of making the child an integral being with the ability to decode multiple areas of knowledge. Keywords: reading, imagination, creativity, parental support, pedagogical strategies school text, production of school text.